Raman spectroscopy of natural and cultured pearls and pearl producing mollusc shells. (18th July 2019) - Karampelas, Stefanos; Fritsch, Emmanuel; Makhlooq, Fatema; Mohamed, Fatima; Al‐Alawi, Abeer
Abstract: The attractiveness of natural and cultured pearls is related, in part, to their colour. Raman spectroscopy was applied to natural and cultured pearls and the shells from 23 species of pearl producing molluscs, thus covering the majority of the natural and cultured pearls and their host animals found in the market today, in order to better understand their colouration and eventually to be able to identify the host animal. Pigments with a polyenic chain were identified in samples from 18 species. The vast majority were found to be a mixture of partially methylated polyenes, similar to those observed in octocorals. Samples with a similar colour but from different animal species can be sometimes related to a significantly different mixtures of such pigments. Only natural pearls from Pinna nobilis were found to be coloured by carotenoids. Raman spectra of other pigments were also observed on samples from four species, possibly linked with pigments from the porphyrin group. Abstract : Natural and cultured pearls and the shells from 23 species of pearl producing molluscs were studied by using Raman spectroscopy. Samples from sixteen species found to be aragonitic with partially methylated polyenic pigments, from one species calcitic with similar pigments and from one species calcitic with fully methylated polyenes (carotenoids). Samples from four species found to contain aragonite along with pigments possibly from the porphyrin family.